2019
DOI: 10.1371/journal.pone.0211111
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 infection increases microRNAs that inhibit Dicer1, HRB and HIV-EP2, thereby reducing viral replication

Abstract: HIV-1 is the causative agent of AIDS (Autoimmune Deficiency Syndrome). HIV-1 infection results in systemic CD4+ T cell depletion, thereby impairing cell-mediated immunity. MicroRNAs are short (~22 nucleotides long), endogenous single-stranded RNA molecules that regulate gene expression by binding to the 3' untranslated regions (3' UTR) of mRNA transcripts. The relation between HIV-1 infection and human miRNA expression profile has been previously investigated, and studies have shown that the virus can alter mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…The work of Telwatte et al (2018) and Yukl et al (2018) and also of Pace et al (2012) have highlighted the importance of post-transcriptional blocks in HIV-1 latency. Post-transcriptional blocks of the nuclear export of various viral transcripts including unspliced, partially spliced, multiply-spliced, and translation of HIV-1 RNA by miRNAs have also been reported (Pomerantz et al, 1990;Malim and Cullen, 1991;Lassen et al, 2006;Weng et al, 2014;Modai et al, 2019). Interestingly, a recent study from the group of Alessandro Marcello has demonstrated that the expression level of MATR3 and PSF, two known posttranscriptional cofactors of the HIV-1 protein Rev required for Rev-mediated export of RRE-containing HIV-1 RNAs (Kula et al, 2011(Kula et al, , 2013, are poorly expressed in latently-infected patients cells (Sarracino et al, 2018), suggesting a novel posttranscriptional block linked to RNA export.…”
Section: Complexity Of Molecular Mechanisms Regulating Hiv-1 Latencymentioning
confidence: 98%
“…The work of Telwatte et al (2018) and Yukl et al (2018) and also of Pace et al (2012) have highlighted the importance of post-transcriptional blocks in HIV-1 latency. Post-transcriptional blocks of the nuclear export of various viral transcripts including unspliced, partially spliced, multiply-spliced, and translation of HIV-1 RNA by miRNAs have also been reported (Pomerantz et al, 1990;Malim and Cullen, 1991;Lassen et al, 2006;Weng et al, 2014;Modai et al, 2019). Interestingly, a recent study from the group of Alessandro Marcello has demonstrated that the expression level of MATR3 and PSF, two known posttranscriptional cofactors of the HIV-1 protein Rev required for Rev-mediated export of RRE-containing HIV-1 RNAs (Kula et al, 2011(Kula et al, , 2013, are poorly expressed in latently-infected patients cells (Sarracino et al, 2018), suggesting a novel posttranscriptional block linked to RNA export.…”
Section: Complexity Of Molecular Mechanisms Regulating Hiv-1 Latencymentioning
confidence: 98%
“…In addition, miR-378g was also found to target 4 confidently annotated sites in 3′ UTR of human HIV-1 enhancer binding protein 3 (HIVEP3) (ENST00000372583.1) located at 582-588, 2026-2032, 2208-2214 and 2580-2586 nucleotides (data not shown). Although, the role of HIVEP3 in HIV-1 replication is not clear, targeting HIVEP2 by miRNAs is known to reduce HIV-1 replication 87 . The effect of miR-378g on HIV-1 replication and MTCT must be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-378 g was also found to target 4 confidently annotated sites in 3'UTR of human HIV-1 enhancer binding protein 3 (HIVEP3) (ENST00000372583.1) located at 582-588, 2026-2032, 2208-2214 and 2580-2586 nucleotides (data not shown). Although, role of HIVEP3 in HIV-1 replication is not clear, targeting HIVEP2 by miRNAs is known to reduce HIV-1 replication [62]. The effect of miR-378 g on HIV-1 replication and MTCT must be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%